Student-lecturer appointment management system - Nor Azrina, Abdol Aziz (2018)
In this era, technology is very important to ease the human matter. An efficient appointment management system can provide better services for user. Unfortunately, the usage of this system for student and lecturer is not provided in Universiti Malaysia Pahang (UMP). It is because whenever students want to make an appointment with lecturer, they still need to message, email, whatsapp or even need to go to the lecturer’s room to make an appointment. This project, named Student-Lecturer Appointment Management System (SLAMS) is aimed to computerize the system including all information about the appointment for lecturer and student. Throughout studies and investigation were conducted on the current manual process and similar or related management system through the internet to expand the understanding of the implementation of the computerized system on appointment. To develop SLAMS, the methodology used is Rapid Application Development (RAD) and the language used is PHP and SQL as the database for the system. This thesis provided an explanation of the background study on the system, the methodology used, system analysis, system design and system development of the system.